2019
DOI: 10.22146/ijc.34440
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gold Nanoparticles Capped-Benzoic Acid Derivative Compounds (<i>o</i>-, <i>m</i>-, and <i>p</i>-Hydroxybenzoic Acid)

Abstract: The effect of a hydroxyl functional group of the benzoic acid derivative compound, i.e. o-hydroxybenzoic acid, m-hydroxybenzoic acid, and p-hydroxybenzoic acid on the synthesis of AuNPs has been studied. It was revealed that the pH, heating time, the concentration of capping agent and the concentration of Au3+ affected the formation of AuNPs. We discovered that o-hydroxybenzoic acid possessed the highest stability, yet it needed the highest concentration of Au3+ and faster reaction time than p-hydroxybenzoic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A researcher has discovered that AuNPs used o-hydroxybenzoic acid possessed the highest stability than p, m-hydroxybenzoic acid-AuNPs also has the smaller sized and unaggregated AuNPs. They also confirmed that the hydroxyl group of o, m, p-hydroxybenzoic acid was responsible for the reduction of Au 3+ to Au 0 [8]. Additionally, sodium acetate has been used to modify the TiO2 particle shape from cube to ellipsoid in the alkaline solution and explained this change due to adsorption of acetate ions onto the surface of TiO2 particle [9].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…A researcher has discovered that AuNPs used o-hydroxybenzoic acid possessed the highest stability than p, m-hydroxybenzoic acid-AuNPs also has the smaller sized and unaggregated AuNPs. They also confirmed that the hydroxyl group of o, m, p-hydroxybenzoic acid was responsible for the reduction of Au 3+ to Au 0 [8]. Additionally, sodium acetate has been used to modify the TiO2 particle shape from cube to ellipsoid in the alkaline solution and explained this change due to adsorption of acetate ions onto the surface of TiO2 particle [9].…”
Section: Introductionmentioning
confidence: 70%
“…They also found that the size of NPs was smaller, and the shape was more rounded when the pH was increased. In the same way, the basic condition makes the capping agent carry a negative charge (such as R-COO and R-O) and this capping agent binds and stabilizes the metal NPs [8]. From Figs.…”
Section: Effect Of Ph On the Stability Of Aunpsmentioning
confidence: 87%
“…In addition to these, individually these compounds could have promoted the development of trigonal, hexagonal and such other anisotropic AuNSs formation. For example, 3‐hydroxybenzoic acid was only present in the dandelion medium, and that can drive AuNSs have large trigonal and hexagonal morphologies [38] . Similarly, the dandelion extracts had very high amount of chlorogenic acid, which triggers anisotropic AuNSs formation (e. g. trigonal, hexagonal, flower etc.)…”
Section: Resultsmentioning
confidence: 99%
“…For example, 3-hydroxybenzoic acid was only present in the dandelion medium, and that can drive AuNSs have large trigonal and hexagonal morphologies. [38] Similarly, the dandelion extracts had very high amount of chlorogenic acid, which triggers anisotropic AuNSs formation (e. g. trigonal, hexagonal, flower etc.). [39,40] By comparing Table 2 and Table 3, excess amount of chlorogenic acid consumed during D-AgNSs and D-AuNS formation.…”
Section: Chemistryselectmentioning
confidence: 99%
“…o-HBA was chosen as the reducing agent of AuNPs due to its ability to convert Au 3+ to Au 0 with an optimization peak which is found in o-HBA at pH 12 [27]. α-and β-CDs were selected as a stabilizer because CDs are hollow compounds that have steric hindrance, so they can stabilize the nanoparticles.…”
Section: Synthesis Of Aunps-cdsmentioning
confidence: 99%